Mineralización del nitrógeno y generación de CO2 por descomposición del estiércol ovino. Altiplano central, Bolivia - Miranda C., Roberto; Alavi M., Gavi; Aliaga Z., Silvia; Caballero, Aylin (Venesuelos, 2014)
<!–[if !mso]> <![endif]–> <!–[if pub]> <b:Publication type="OplPub" oty="68" oh="256"> <b:OhPrintBlock priv="30E">281</b:OhPrintBlock> <b:NuDefaultUnits priv="1004">1</b:NuDefaultUnits> <b:DptlPageDimensions type="OplPt" priv="1211"> <b:Xl priv="104">7772400</b:Xl> <b:Yl priv="204">10058400</b:Yl> </b:DptlPageDimensions> <b:DxlDefaultTab priv="1504">359410</b:DxlDefaultTab> <b:OhGallery priv="180E">259</b:OhGallery> <b:OhFancyBorders priv="190E">261</b:OhFancyBorders> <b:OhCaptions priv="1A0E">257</b:OhCaptions> <b:OhQuillDoc priv="200E">276</b:OhQuillDoc> <b:OhMailMergeData priv="210E">262</b:OhMailMergeData> <b:OhColorScheme priv="220E">279</b:OhColorScheme> <b:DwNextUniqueOid priv="2304">1</b:DwNextUniqueOid> <b:IdentGUID priv="2A07">0``````````````````````</b:IdentGUID> <b:DpgSpecial priv="2C03">5</b:DpgSpecial> <b:CTimesEdited priv="3C04">1</b:CTimesEdited> <b:NuDefaultUnitsEx priv="4104">1</b:NuDefaultUnitsEx> <b:OhImpositionEngine priv="440E">285</b:OhImpositionEngine> </b:Publication> <b:PrinterInfo type="OplPrb" oty="75" oh="281"> <b:OhColorSepBlock priv="30E">282</b:OhColorSepBlock> <b:OpmOutsidePrintMode priv="B04">1</b:OpmOutsidePrintMode> <b:FInitComplete priv="1400">False</b:FInitComplete> <b:DpiX priv="2203">0</b:DpiX> <b:DpiY priv="2303">0</b:DpiY> <b:DxlOverlap priv="2404">0</b:DxlOverlap> <b:DylOverlap priv="2504">0</b:DylOverlap> </b:PrinterInfo> <b:ColorSeperationInfo type="OplCsb" oty="79" oh="282"> <b:Plates type="OplCsp" priv="214"> <b:OplCsp type="OplCsp" priv="11"> <b:EcpPlate type="OplEcp" priv="213"> <b:Color priv="104">-1</b:Color> </b:EcpPlate> </b:OplCsp> </b:Plates> <b:DzlOverprintMost priv="304">304800</b:DzlOverprintMost> <b:CprOverprintMin priv="404">243</b:CprOverprintMin> <b:FKeepawayTrap priv="700">True</b:FKeepawayTrap> <b:CprTrapMin1 priv="904">128</b:CprTrapMin1> <b:CprTrapMin2 priv="A04">77</b:CprTrapMin2> <b:CprKeepawayMin priv="B04">255</b:CprKeepawayMin> <b:DzlTrap priv="C04">3175</b:DzlTrap> <b:DzlIndTrap priv="D04">3175</b:DzlIndTrap> <b:PctCenterline priv="E04">70</b:PctCenterline> <b:FMarksRegistration priv="F00">True</b:FMarksRegistration> <b:FMarksJob priv="1000">True</b:FMarksJob> <b:FMarksDensity priv="1100">True</b:FMarksDensity> <b:FMarksColor priv="1200">True</b:FMarksColor> <b:FLineScreenDefault priv="1300">True</b:FLineScreenDefault> </b:ColorSeperationInfo> <b:TextDocProperties type="OplDocq" oty="91" oh="276"> <b:OhPlcqsb priv="20E">278</b:OhPlcqsb> <b:EcpSplitMenu type="OplEcp" priv="A13"> <b:Color>134217728</b:Color> </b:EcpSplitMenu> </b:TextDocProperties> <b:StoryBlock type="OplPlcQsb" oty="101" oh="278"> <b:IqsbMax priv="104">1</b:IqsbMax> <b:Rgqsb type="OplQsb" priv="214"> <b:OplQsb type="OplQsb" priv="11"> <b:Qsid priv="104">3</b:Qsid> <b:TomfCopyfitBase priv="80B">-9999996.000000</b:TomfCopyfitBase> <b:TomfCopyfitBase2 priv="90B">-9999996.000000</b:TomfCopyfitBase2> <b:DzlHotZone priv="A04">229870</b:DzlHotZone> </b:OplQsb> </b:Rgqsb> </b:StoryBlock> <b:ColorScheme type="OplSccm" oty="92" oh="279"> <b:Cecp priv="104">8</b:Cecp> <b:Rgecp type="OplEcp" priv="214"> <b:OplEcp priv="F">Empty</b:OplEcp> <b:OplEcp type="OplEcp" priv="111"> <b:Color>16711680</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="211"> <b:Color>52479</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="311"> <b:Color>26367</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="411"> <b:Color>13421772</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="511"> <b:Color>16737792</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="611"> <b:Color>13382502</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="711"> <b:Color>16777215</b:Color> </b:OplEcp> </b:Rgecp> <b:SzSchemeName priv="618">Azulejo</b:SzSchemeName> </b:ColorScheme> <![if pub11]> <![endif]> <![endif]–><!–[if pub]> <b:Page type="OplPd" oty="67" oh="265"> <b:PtlvOrigin type="OplPt" priv="511"> <b:Xl>22860000</b:Xl> <b:Yl>22860000</b:Yl> </b:PtlvOrigin> <b:Oid priv="605">(`@`````````</b:Oid> <b:OhoplWebPageProps priv="90E">266</b:OhoplWebPageProps> <b:OhpdMaster priv="D0D">263</b:OhpdMaster> <b:PgtType priv="1004">5</b:PgtType> <b:PtlvOriginEx type="OplPt" priv="1111"> <b:Xl>110185200</b:Xl> <b:Yl>110185200</b:Yl> </b:PtlvOriginEx> </b:Page> <![endif]–><!–[if gte mso 9]> <![endif]–> <span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">El objetivo del presente trabajo fue evaluar la mineralización del nitrógeno y producción de CO<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD"> 2<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD"> como resultado de la incorporación de estiércol fresco de ovino al suelo. El diseño experimental utilizado fue completamente al azar con ocho tratamientos y tres repeticiones. Los tratamientos fueron: suelo, 0, 4, 8, 12, 16, 20, 24 y 30 Mg de estiércol por hectárea. La temperatura se mantuvo entre los 12 a 15 oC en una cámara de incubación. El nitrógeno como NH<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD"> 4<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD"> y NO<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">3<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">+NO<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">2<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD"> fueron determinados a los 1, 15, 22, 29, 43, 57 y 71 días luego de la incubación. El CO<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">2<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD"> fue evaluado a los 1, 8, 15, 22, 34, 48, 62, 76 y 92 días luego de la incubación. Los resultados muestran que hubo una inmovilización del nitrógeno en las cinco primeras semanas, para luego dar paso a la mineralización. Al inicio se encontraron mayores concentraciones de N-NH<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">4<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">, la misma disminuyó ligeramente en el tiempo, mientras que la nitrificación se inicio a partir del día 57. Los tratamientos con aplicaciones de 16 a 24 Mg de estiércol fueron los que presentaron mayor tasa de nitrificación llegando a 0,7 y 0,94 kg ha<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">-1 <span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">día<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">-1 <span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; language: es-TRAD; mso-ansi-language: es-TRAD; mso-font-width: 97%; mso-ligatures: none;" lang="es-TRAD">de nitrógeno mineral respectivamente. Las concentraciones de dióxido de carbono se incrementan a medida que se introducen al suelo mayores niveles de estiércol, lo que denota una creciente actividad biológica con la adición del insumo orgánico. Palabras clave: Mineralización del nitrógeno; abonamiento orgánico; dinámica del nitrógeno; producción de CO2; descomposición del estiércol. Abstract <!–[if !mso]> <![endif]–> <!–[if pub]> <b:Publication type="OplPub" oty="68" oh="256"> <b:OhPrintBlock priv="30E">281</b:OhPrintBlock> <b:NuDefaultUnits priv="1004">1</b:NuDefaultUnits> <b:DptlPageDimensions type="OplPt" priv="1211"> <b:Xl priv="104">7772400</b:Xl> <b:Yl priv="204">10058400</b:Yl> </b:DptlPageDimensions> <b:DxlDefaultTab priv="1504">359410</b:DxlDefaultTab> <b:OhGallery priv="180E">259</b:OhGallery> <b:OhFancyBorders priv="190E">261</b:OhFancyBorders> <b:OhCaptions priv="1A0E">257</b:OhCaptions> <b:OhQuillDoc priv="200E">276</b:OhQuillDoc> <b:OhMailMergeData priv="210E">262</b:OhMailMergeData> <b:OhColorScheme priv="220E">279</b:OhColorScheme> <b:DwNextUniqueOid priv="2304">1</b:DwNextUniqueOid> <b:IdentGUID priv="2A07">0``````````````````````</b:IdentGUID> <b:DpgSpecial priv="2C03">5</b:DpgSpecial> <b:CTimesEdited priv="3C04">1</b:CTimesEdited> <b:NuDefaultUnitsEx priv="4104">1</b:NuDefaultUnitsEx> <b:OhImpositionEngine priv="440E">285</b:OhImpositionEngine> </b:Publication> <b:PrinterInfo type="OplPrb" oty="75" oh="281"> <b:OhColorSepBlock priv="30E">282</b:OhColorSepBlock> <b:OpmOutsidePrintMode priv="B04">1</b:OpmOutsidePrintMode> <b:FInitComplete priv="1400">False</b:FInitComplete> <b:DpiX priv="2203">0</b:DpiX> <b:DpiY priv="2303">0</b:DpiY> <b:DxlOverlap priv="2404">0</b:DxlOverlap> <b:DylOverlap priv="2504">0</b:DylOverlap> </b:PrinterInfo> <b:ColorSeperationInfo type="OplCsb" oty="79" oh="282"> <b:Plates type="OplCsp" priv="214"> <b:OplCsp type="OplCsp" priv="11"> <b:EcpPlate type="OplEcp" priv="213"> <b:Color priv="104">-1</b:Color> </b:EcpPlate> </b:OplCsp> </b:Plates> <b:DzlOverprintMost priv="304">304800</b:DzlOverprintMost> <b:CprOverprintMin priv="404">243</b:CprOverprintMin> <b:FKeepawayTrap priv="700">True</b:FKeepawayTrap> <b:CprTrapMin1 priv="904">128</b:CprTrapMin1> <b:CprTrapMin2 priv="A04">77</b:CprTrapMin2> <b:CprKeepawayMin priv="B04">255</b:CprKeepawayMin> <b:DzlTrap priv="C04">3175</b:DzlTrap> <b:DzlIndTrap priv="D04">3175</b:DzlIndTrap> <b:PctCenterline priv="E04">70</b:PctCenterline> <b:FMarksRegistration priv="F00">True</b:FMarksRegistration> <b:FMarksJob priv="1000">True</b:FMarksJob> <b:FMarksDensity priv="1100">True</b:FMarksDensity> <b:FMarksColor priv="1200">True</b:FMarksColor> <b:FLineScreenDefault priv="1300">True</b:FLineScreenDefault> </b:ColorSeperationInfo> <b:TextDocProperties type="OplDocq" oty="91" oh="276"> <b:OhPlcqsb priv="20E">278</b:OhPlcqsb> <b:EcpSplitMenu type="OplEcp" priv="A13"> <b:Color>134217728</b:Color> </b:EcpSplitMenu> </b:TextDocProperties> <b:StoryBlock type="OplPlcQsb" oty="101" oh="278"> <b:IqsbMax priv="104">1</b:IqsbMax> <b:Rgqsb type="OplQsb" priv="214"> <b:OplQsb type="OplQsb" priv="11"> <b:Qsid priv="104">4</b:Qsid> <b:TomfCopyfitBase priv="80B">-9999996.000000</b:TomfCopyfitBase> <b:TomfCopyfitBase2 priv="90B">-9999996.000000</b:TomfCopyfitBase2> <b:DzlHotZone priv="A04">229870</b:DzlHotZone> </b:OplQsb> </b:Rgqsb> </b:StoryBlock> <b:ColorScheme type="OplSccm" oty="92" oh="279"> <b:Cecp priv="104">8</b:Cecp> <b:Rgecp type="OplEcp" priv="214"> <b:OplEcp priv="F">Empty</b:OplEcp> <b:OplEcp type="OplEcp" priv="111"> <b:Color>16711680</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="211"> <b:Color>52479</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="311"> <b:Color>26367</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="411"> <b:Color>13421772</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="511"> <b:Color>16737792</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="611"> <b:Color>13382502</b:Color> </b:OplEcp> <b:OplEcp type="OplEcp" priv="711"> <b:Color>16777215</b:Color> </b:OplEcp> </b:Rgecp> <b:SzSchemeName priv="618">Azulejo</b:SzSchemeName> </b:ColorScheme> <![if pub11]> <![endif]> <![endif]–><!–[if pub]> <b:Page type="OplPd" oty="67" oh="265"> <b:PtlvOrigin type="OplPt" priv="511"> <b:Xl>22860000</b:Xl> <b:Yl>22860000</b:Yl> </b:PtlvOrigin> <b:Oid priv="605">(`@`````````</b:Oid> <b:OhoplWebPageProps priv="90E">266</b:OhoplWebPageProps> <b:OhpdMaster priv="D0D">263</b:OhpdMaster> <b:PgtType priv="1004">5</b:PgtType> <b:PtlvOriginEx type="OplPt" priv="1111"> <b:Xl>110185200</b:Xl> <b:Yl>110185200</b:Yl> </b:PtlvOriginEx> </b:Page> <![endif]–><!–[if gte mso 9]> <![endif]–> <span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">The purpose of this study was to evaluate the nitrogen mineralization and CO<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">2<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US"> production as a result of incorporation of fresh sheep manure to the soil. The experimental design was completely randomized with eight treatments and three replications. The selected treatments were: 0, 4, 8, 12, 16, 20, 24 and 30 Mg ha-1 of manure. The temperature was maintained between 12 and 15° C in an incubation chamber. Nitrogen as NH<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">4<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US"> and NO<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">3<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US"> + NO<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">2<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US"> were determined at 1, 15, 22, 29, 43, 57 and 71 days after starting the incubation. The CO<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">2<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US"> was measured at 1, 8, 15, 22, 34, 48, 62, 76 and 92 days after incubation. The results show that there was nitrogen immobilization in the first 5 weeks and then gave way to the mineralization. At the beginning concentrations of N-NH<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">4<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US"> increased but it decreased slightly over time, whereas nitrification was started from day 57. The treatments with applications of 16 and 24 Mg of manure showed a higher rate of nitrification, reaching 0,7 and 0,94 kg ha<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">-1 <span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">day<span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">-1 <span style="font-family: Arial; mso-default-font-family: Arial; mso-ascii-font-family: Arial; mso-latin-font-family: Arial; mso-greek-font-family: Arial; mso-cyrillic-font-family: Arial; mso-armenian-font-family: Arial; mso-hebrew-font-family: Arial; mso-arabic-font-family: Arial; mso-currency-font-family: Arial; mso-latinext-font-family: Arial; color: black; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-ligatures: none;" lang="en-US">of mineral nitrogen respectively. The carbon dioxide concentrations increased with the application of higher levels of manure into the soil, indicating an increase of the soil biological activity with the addition of organic matter. Keywords: nitrogen mineralization; organic fertilization; dynamic of nitrogen; CO2 production; manure decomposition.